The feasibility of testing otoliths and semicircular canals function using VEMPs and vHIT in Malaysian children - Nurul Ain Abdullah,; Nor Haniza Abdul Wahat,; Curthoys, Ian S.; Asma Abdullah,; Hamidah Alias, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Early identification of any vestibular dysfunction and balance problem in children is crucial for their general well-being. However the identification process, could be challenging and difficult as compared to adults. We conducted a preliminary study to review our initial experience with ocular and cervical vestibular evoked myogenic potentials (oVEMPs and cVEMPs), video head impulse test (vHIT) and Bruininks Oseretsky Test of Motor Proficiency II (BOT-2) on healthy children and also to determine the feasibility of these tests in this population. Twenty one normal healthy children (12 boys and 9 girls), aged between 6 and 15 years old (mean age, 11.15 ± 2.54 years) participated in the study. They underwent oVEMPs and cVEMPs elicited with bone conduction stimulus via minishaker and air conduction stimulus respectively. All six semicircular canals were assessed using the vHIT. Bilateral coordination, balance, running, speed and agility which are the three subsets of BOT-2 gross motor assessment were conducted for balance assessment. All subjects completed the vestibular and balance assessment except for 1 subject who did not complete the vHIT vertical component. The response rate was 100% for oVEMPs, cVEMPs, and BOT-2, and 95.24% for vHIT. The mean latency and mean amplitude for n10 oVEMPs were 8.88 ± 0.92 and 2.71 ± 1.29, respectively. The mean latency for cVEMPs p13, and n23 were 13.4 ± 1.35 and 21.76 ± 3.71, respectively with interamplitude mean of 97.57 ± 42.69. The vHIT mean for vestibular ocular reflex (VOR) gain were >0.85 for lateral canals and > 0.65 for vertical canals. The mean scale score for bilateral coordination, balance, running, speed, and agility for BOT-2 were 17.52 ± 3.40, 15.14 ± 3.65 and 13.9 ± 5.46, respectively. This study suggest that VEMPs, vHIT, and BOT-2 are feasible test for vestibular and balance assessment in children. Apart from the tests findings, it is hoped that the described experienced and adjustment made in assessing this young population could also be applied by other relevant professionals.